PEMBELAJARAN KETERAMPILAN BERPIKIR KRITIS: STUDI KASUS DI MIM NGIPIK DAN MIM DONDONG KULONPROGO - Andi Prastowo; Mujadi Mujadi; Purnaida Purnaida; Bayu Rahmad Santosa (Sekolah Tinggi Agama Islam Negeri (STAIN) Kudus, 2019)
The services of Islamic educational institutions in Indonesia must be able to adjust to the demands and needs of the surrounding environment, including in the current context of 21st century skills, so that the institution can remain competitive and survive in the era of globalization. Madrasah Ibtidaiyah Ma'arif (MIM) Ngipik and MIM Dondong in Kulonprogo District Special Province of Yogyakarta are some Islamic educational institutions in the formal education path that has been trying to cultivate 21st century skills especially critical thinking skills. This article aims to reveal about how to learn critical thinking (CT) in MIM Ngipik and MIM Dondong as well as what critical thinking skills are successfully grown in learning in the madrasah. This research uses qualitative paradigm and case study method. The results of this study indicate that critical thinking learning (CTL) is done by multi-method learning and classroom management varied. The critical thinking skills of students that can be grown are: able to ask questions that match the topic discussed, began to be able to collect relevant information; begin to learn to act efficiently and creatively based on information in teacher guidance; can put forward quite a logical argument based on factual information in teacher guidance, can take credible conclusions with group work and in teacher guidance, and begin to be able to think analysis on differentiating cognitive processes.